Factors Responsible for Joining MLM Business and Relation of Mode of Association with Networker’s Satisfaction - Ashok Kumar; Akshay Kumar Satsangi (INTERNATIONAL RESEARCH JOURNAL OF BUSINESS STUDIES, 2021)
This study focuses on identifying factors responsible for joining Multi-Level Marketing (MLM) business by the networkers and analysis of satisfaction level of networkers with respect to the mode of association with MLM business. A quantitative methodology with a survey technique was used on 305 selected networkers who operate their MLM business from Kanpur city. Factors responsible for encouraging people to join the MLM business as a networker are explored by the factor analytical approach. An independent T-test was employed to test the proposed hypothesis. This study found that earn income for meeting expenses, source of residual income, low investment and low risk, more leisure time, personality development, better lifestyle, enhance social interaction, and helping others are the key factors that motivate the networkers to join MLM business. Moreover, the networkers involved in MLM business through any mode of the association are equally satisfied with this business. https://doi.org/10.21632/irjbs.14.1.49-57